Applied statistics in business and economics - Doane, David P.; Seward, Lori E. (The McGraw-Hill/Irwin series, operations and decision sciences, 2011)
Offers an introduction to Statistics concepts and applications in business and economics. This title features online supplements that emphasize thinking about data, choosing appropriate data analytic tools, and using computers effectively. It demonstrates the software techniques using the common software